Pengembangan Administrasi Hubungan Sekolah dan Masyarakat Berbasis Teknologi Informasi di Era Society 5.0 - Wahyuni, Putri; Astuti, Lucky; Sabri, Ahmad; Hidayatullah, Rully (Journal Innovation In Education, 2024)
The development of school and community relations administration based on communication strategies in the Society 5.0 era emphasizes the importance of collaboration between educational institutions and communities to achieve better educational goals. In this context, effective communication is the key to building harmonious and mutually beneficial relationships. Schools need to adopt a participatory approach that involves all stakeholders, including students, parents, and community members, to create learning environments that are inclusive and responsive to local needs. The aim of this research is to analyze the development of Information Technology-based administration of school and community relations in the Society 5.0 era. The research method used is library research. The research results show that the development of administration of school and community relations is based on Information Technology in the Society 5.0 era. By utilizing technology and digital platforms, schools can increase community interaction and involvement, as well as facilitate transparent exchange of information. A good communication strategy not only strengthens relationships, but also supports the development of relevant and sustainable programs, thereby creating synergy between education and community development. This is in line with the principles of Society 5.0 which emphasizes integration between technology and social values to improve people's quality of life.